O acolhimento familiar e a corresponsabilização da comunidade no processo de proteção de crianças e adolescentes - Silva, Melissa Pinheiro Barros da (2024)
This article aims to find ways to involve the community in the process of protection of children and adolescents in foster care situations. The study provides a historical analysis of the Doctrine of the Irregular Situation in opposition to the Doctrine of Integral Protection, seeking to explain how the Family Reception provided for in the Law, as well as revealing the importance of the family for development psychological, emotional, physical and intellectual of children and adolescents in the development phase. It is understood that Family Reception is a more efficient option, to the detriment of Institutional Reception, due to its form of private and individualized care within a family. This institute provides care for children in vulnerable situations and their reintegration, when possible, into their family of origin, helping them their needs, in order to minimize the problems that caused the separation.